Droit conjugal et unions de même sexe : mariage, partnariat et concubinage dans neuf pays européens - Waaldijk, Kees; Fassin, Eric; Digoix, Marie (Paris : PUF, 2008)
Fonds Suzan Daniel (FSD)
Frans
Monografie